Professional and Support Staff in Higher Education (University Development and Administration,, 2018)
This volume, Professional and Support Staff in Higher Education, is focused on the issues and experiences of professional and support staff in higher education. The 29 chapters of this book span a broad range of topic areas, ranging across professional practices and identity, leadership and inclusion in higher education, professional development, and how the current higher education landscape impacts on their work, careers, aspirations and performance. The broad aims of this book are twofold: to contribute to the limited body of knowledge regarding professional and support staff in higher education, and to explore the key issues facing these professionals today through their own contributions. Professional and support staff are one of the universities' most valuable assets, as they hold much of the corporate knowledge required to ensure that universities operate efficiently and effectively. The increasing professionalization of university professional staff has impacted on the roles they currently perform, as more professionals now occupy senior executive positions within universities; positions there were previously occupied by senior academics. Similarly, the boundaries between some professional and academic roles have blurred, creating a sub-category; the para-academic staff. Given the contribution professional and support staff make, and the increasing importance of the roles they perform within their institutions and to the society as a whole, it is surprising that their work, impact, careers, and aspirations remain largely unexplored in the literature and research to date. We hope readers find this book useful and insightful, that it enables greater and deeper insight among and between professional staff and their institutions, and that it contributes meaningfully to the growing body of knowledge and scholarship regarding professional and support staff in higher education globally. We also hope that the book assists in raising awareness about the professions that are part of our educational institutions, and the contributions that they make not only to their organisations, but to society as a whole. .